2011
DOI: 10.2217/pgs.11.34
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone-Induced Changes in Gene-Expression Profiles in Healthy Volunteers

Abstract: The identified gene signatures provide new starting points for further study into GC-induced transcriptional regulation in vivo and the mechanisms underlying GC-mediated metabolic side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Rapid non-genomic effects of GR ligation occur after ligand-induced dissociation of the GR multiprotein complex in the cytoplasm (39). This diversity of regulatory processes indicates that prednisolone is likely to regulate different genes than the physiological glucocorticoid, hydrocortisone (41). …”
Section: Discussionmentioning
confidence: 99%
“…Rapid non-genomic effects of GR ligation occur after ligand-induced dissociation of the GR multiprotein complex in the cytoplasm (39). This diversity of regulatory processes indicates that prednisolone is likely to regulate different genes than the physiological glucocorticoid, hydrocortisone (41). …”
Section: Discussionmentioning
confidence: 99%
“…Relationships between keywords can be summarized in tables that can be sorted and filtered based on scoring schemas yielding ranked lists of genes, drugs or diseases which can be used for guiding follow up experiments [51,79,80]. It is important to link the keywords and concepts in these results back to the original text source where they can be highlighted in the text, providing the context in which they are mentioned [9,81].…”
Section: Visualizationmentioning
confidence: 99%
“…Toonen et al [79] used CoPub (Table 1) to analyze a set of genes that was differentially expressed in blood of healthy volunteers treated with prednisolone. They matched all genes against three keyword categories, i.e.…”
Section: Genome and Gene Expression Annotationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for most tracers this correlation is less clear. For instance, Steffens et al have studied the correlation between the radiolabeled antibody cG250 ( 131 I-cG250) and the expression of its respective antigen carbonic anhydrase IX (CAIX) [33]. They have shown that high antigen expression was a prerequisite for high antibody uptake.…”
Section: Factors Affecting Imaging Of Drug Deliverymentioning
confidence: 99%